Antibacteria Susceptibility Test of Garlic (Allium sativum L.) Against Enterococcus faecalis As Root Canal Medicament - Nabilla Syaidah Ageng Kuswandi; Gita Tarigan; Dicha Yuliadewi Rahmawati (Al Makki Publisher, 2025)
This study aims to investigate the effect of garlic extract (GE) on the inhibition of Enterococcus faecalis (EF) bacterial growth. This study is a laboratory experimental research with a true experimental post-test only control group design, conducted in vitro using the well diffusion method. The experimental group consists of EF bacteria treated with different concentrations of GE, while the control group consists of EF bacteria treated with 0.2% chlorhexidine (CHX) as the positive control (PC) and 10% dimethyl sulfoxide (DMSO) as the negative control (NC). This study aims to observe the inhibition zone diameter (IZD) of bacterial growth after treatment with different concentrations of GE or control agents, measured in millimeters using a caliper. Phytochemical test revealed that the GE used in this study contains secondary metabolite compounds such as phenolics, flavonoids, saponins, and steroids, resulting in an IZD of 5.85 ± 0.26 at 100% GE and 3.25 ± 0.27 at 75% GE. The IZD formed on PC was 17.34 ± 0.33, and no IZD was formed on 50% GE or NC. The effect of GE in inhibiting the growth of EF was observed by the presence of inhibition zones at 100% and 75% concentrations, although it was not yet able to match the effectiveness of 0.2% CHX.